Prevalence of complications and comorbidities associated with obesity: a health insurance claims analysis - Jay P. Bae; David R. Nelson; Kristina S. Boye; Kieren J. Mather (BMC Public Health)
Abstract Background Despite the substantial burden of obesity in the United States (US), data on the comprehensive range of comorbidities in different age groups is limited. This study assessed the prevalence of various comorbidities among people diagnosed with obesity (as per ICD-10 diagnosis code) across age cohorts and compared how they differ from people without obesity. Methods This cross-sectional study analyzed individuals from all four regions (Midwest, Northeast, South, and West) of the US who had continuous insurance coverage from 2018 to 2020, using a large health insurance claims database (Merative™ MarketScan®). Identification of disorders relied on ICD-10 diagnosis code in patient claims and their prevalence was calculated. Results Of 6,935,911 individuals, people with a diagnosis of obesity accounted for 22.0%, 33.6%, and 34.4% in the 18–39 years, 40–64 years, and ≥ 65 years age groups, respectively. Within age strata, the mean age of people with obesity was comparable with those without obesity. Comorbidity burden was significantly higher among people with obesity, but increased with age in both obesity and non-obesity groups. Comorbidities with highest prevalence in people with obesity included: (i) hypertension (18–39 years: 29.0%, 40–64 years: 66.2%, ≥ 65 years: 89.4%), (ii) dyslipidemia (18–39 years: 28.1%, 40–64 years: 65.4%, ≥ 65 years: 88.0%), (iii) depression or anxiety (18–39 years: 44.1%, 40–64 years: 39.0%, ≥ 65 years: 38.9%), and (iv) prediabetes (18–39 years: 17.1%, 40–64 years: 32.2%, ≥ 65 years: 35.3%). Notably, increased prevalence of cardiometabolic risk factors such as hypertension and dyslipidemia began at an earlier age in people with obesity as compared with those without obesity. Ratio of prevalence between obesity and non-obesity groups was highest for the 18–39 years age group, as compared to older groups. Disorders such as obstructive sleep apnea, osteoarthritis, type 2 diabetes, metabolic dysfunction-associated steatotic liver disease, coronary heart diseases (CHD), and chronic kidney diseases also exhibited substantial burden among those with obesity. Conclusions In this claims study, hypertension and dyslipidemia were the leading comorbidities in people with obesity, with an increasing prevalence with age. The burden of cardiometabolic comorbidities among the younger age group suggested potential risk for early onset of CHD in later life. Understanding the range of obesity-related comorbidities seen in this claims data may encourage healthcare professionals and healthcare systems to systematically diagnose and better manage these disorders. Further research using additional data sources can offer a more accurate view of the prevalence of obesity and its impact.